2015
DOI: 10.1891/0730-0832.34.3.165
|View full text |Cite
|
Sign up to set email alerts
|

Review and Critical Analysis of Massage Studies for Term and Preterm Infants

Abstract: Benefits of massage for term infants are: improved weight gain, growth, and sleep and decreased hyperbilirubinemia. Benefits for preterm infants are: improved weight gain, decreased response to pain, and increased interactions with parents. However, the few studies use different interventions related to timing and number of massages, and the outcomes vary among studies. There is not enough evidence to support the use of massage for term and preterm infants, but massage may be considered on a case-by-case basis. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 25 publications
2
22
0
6
Order By: Relevance
“…Other reviews related to neonates focus on developmental care, neurodevelopmentally supportive care or individual interventions. 24,25,28,29 Individualized developmental care is a system of care in which there is continuous assessment of infant behavior mixed with modifications to caregiving of the preterm infant; a clinical practice guideline for individualized developmental care was established in 2007. 121 This work is important, as it aids in the understanding of modifying the environment early in development to support the unique needs of the preterm infant, provides guidance on how to assess and when/how to intervene, gives specific criteria for light levels (cycling, avoiding direct light) and defines maximum intensity (not to exceed 50 decibels) of sound.…”
Section: Discussionmentioning
confidence: 99%
“…Other reviews related to neonates focus on developmental care, neurodevelopmentally supportive care or individual interventions. 24,25,28,29 Individualized developmental care is a system of care in which there is continuous assessment of infant behavior mixed with modifications to caregiving of the preterm infant; a clinical practice guideline for individualized developmental care was established in 2007. 121 This work is important, as it aids in the understanding of modifying the environment early in development to support the unique needs of the preterm infant, provides guidance on how to assess and when/how to intervene, gives specific criteria for light levels (cycling, avoiding direct light) and defines maximum intensity (not to exceed 50 decibels) of sound.…”
Section: Discussionmentioning
confidence: 99%
“…While it does appear to confer some benefit to infants receiving it, massage does not significantly alter long-term neurodevelopmental outcomes and is time consuming. Massage does decrease infant crying, decrease infant pain scores, improve infant weight gain in preterm and low birth weight infants, and potentially decreases their length of stay [ 59 , 77 , 78 ]. Some studies indicate that infant massage improves mother-infant interactions after the massage intervention [ 59 ].…”
Section: Protecting Infant Sleepmentioning
confidence: 99%
“…Massage does decrease infant crying, decrease infant pain scores, improve infant weight gain in preterm and low birth weight infants, and potentially decreases their length of stay [ 59 , 77 , 78 ]. Some studies indicate that infant massage improves mother-infant interactions after the massage intervention [ 59 ]. Additionally, studies of infant massage and gentle human touch found a significant increase in sleep state and a decrease in awake state, both during and after the intervention [ 3 ].…”
Section: Protecting Infant Sleepmentioning
confidence: 99%
“…Его назначение возможно после стабилизации ребенка. Массаж обеспечивает тактильно-кинестетическую стимуляцию и повышает парасимпатическую активность [35][36][37][38]. Во время массажа у недоношенных новорожденных изменяется амплитуда электроэнцефалограмм, на которых преобладают δ-волны.…”
Section: эффекты массажа у новорожденныхunclassified